Invicti bellate RV 628 en sol majeur / Antonio Vivaldi. - Vivaldi, Antonio, 1678-1741 (CLC Productions, 2003)
This video directed by Pampuri, Emmanuel. is a performance of motets and a concerto by Vivaldi.